Model Mutu Berbasis Data untuk Menjembatani Pendidikan Islam Tradisional dan Keterampilan Kontemporer - Tiara Nurul Annisa'; Arini Nuora Darina; Juwita; Toyyibatul Mukminatus Sukriyah; Ahmad Faidul Mannan (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2025)
This study focuses on the dynamics of social and technological change at MA Darun Najjah Lumajang and the madrasa's efforts to maintain the relevance of Islamic education amid the demands of 21st-century skills. In this context, the madrasa faces the challenge of preserving traditional Islamic values while adapting to the digital era and meeting societal expectations for graduates who are not only religious but also professionally competent. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation from five key informants, including the principal, vice principal, teachers, and students. The findings reveal that MA Darun Najjah has begun integrating 21st-century skills into its curriculum through teacher training, the use of digital media, and extracurricular programs. However, challenges remain in areas such as accountability, data-based quality evaluation, and institutional capacity. The implications of this study highlight the need to strengthen a context-based, data-driven educational quality system, enhance teachers’ evaluative capacity, and design an integrative curriculum that combines Islamic values with global demands.